2015
DOI: 10.1007/s00345-015-1692-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinically localized type 1 and 2 papillary renal cell carcinomas have similar survival outcomes following surgery

Abstract: While patients with type 2 PRCC appear to present with more advanced disease than patients with type 1, PRCC subtype does not appear to be an independent predictor of CSS, RFS or OS for treated localized disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
3
20
1
1
Order By: Relevance
“…Papillary RCC (PRCC) is the second most common subtype and accounts for 15% of all cases [2]. PRCC is often subdivided into type 1 and 2, but studies did not confirm the independent prognostic value of PRCC type in localised disease [3, 4]. Compared with conventional clear cell RCC, PRCC is thought to have a more favourable prognosis in the non-metastatic stage [5], while patients with metastatic disease have worse outcomes than their counterparts [6].…”
Section: Introductionmentioning
confidence: 99%
“…Papillary RCC (PRCC) is the second most common subtype and accounts for 15% of all cases [2]. PRCC is often subdivided into type 1 and 2, but studies did not confirm the independent prognostic value of PRCC type in localised disease [3, 4]. Compared with conventional clear cell RCC, PRCC is thought to have a more favourable prognosis in the non-metastatic stage [5], while patients with metastatic disease have worse outcomes than their counterparts [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ledezma et al studied 627 patients with PRCC undergoing surgery and observed that 48 (8%) experienced relapse of which 10 out of 27 patients with papillary type 2 RCC exhibited metastatic disease in the lymph nodes, whereas most patients with type 1 PRCC (11/21) metastasized to the lungs [13].…”
Section: Discussionmentioning
confidence: 99%
“…Ledezma et al . [ 10 ] investigated 627 PRCC patients undergoing surgery and reported that 48 subjects experienced relapse. Ten out of 27 patients with type 2 PRCC exhibited metastatic lymph nodes, whereas most type 1 PRCC patients (11 of 21) reported pulmonary metastases.…”
Section: Discussionmentioning
confidence: 99%